Role of hypoxia in the behaviour, physiology, immunity and response mechanisms of crustaceans: A review - Cheng Zheng; Qianqian Zhao; Erchao Li; Daxian Zhao; Shengming Sun (Reviews in Aquaculture, 2022)
Crustaceans are often exposed to hypoxic stress in intensive aquaculture systems. Such stress leads to physiological, behavioural and biochemical changes, which can cause various metabolic disorders or even death. Crustacean response mechanisms to hypoxia stress are known to be complex, with their regulation involving multiple genes. In this review, after briefly exploring some known causes of hypoxic stress in aquaculture systems, we discuss the physiological adaptation strategies used by crustaceans in response to hypoxia and summarise recent information regarding the effects of hypoxia on the behaviour, survival, antioxidant ability, metabolic processes and innate immunity of crustaceans. In addition, we give particular emphasis to the known molecular mechanisms underlying hypoxia related to the hypoxia‐inducible factor 1 (HIF‐1) signalling pathway, the adenosine 5′‐monophosphate‐activated protein kinase signalling (AMPK) pathway, and apoptosis. Practically, it is clear that multiple measures need to be taken to prevent and regulate the adverse effects of hypoxic stress in intensive aquaculture systems, including development of hypoxia‐resistant breeds and nutritional regulation techniques. Overall, this review provides a theoretical basis for understanding the molecular mechanisms underlying hypoxic stress in crustaceans, while making conceptual connections with data from related study areas in other species.